Results of a pilot study of patient-to-patient education strategy on self-management among glycemic uncontrolled patients with diabetes - Xiang Y; Luo P; Cai X; Tang Y; Wu Z (Patient Preference and Adherence, 2017)
Yingying Xiang, Pingyan Luo, Xueqin Cai, Yuqin Tang, Zhongming Wu Key Laboratory of Hormones and Development (Ministry of Health), Tianjin Key Laboratory of Metabolic Diseases, Tianjin Metabolic Diseases Hospital & Tianjin Institute of Endocrinology, Tianjin Medical University, Tianjin, People’s Republic of China Objectives: The purpose of this study was to assess the efficacy and practicability of patient-to-patient (PTP) education strategy on glycemic control among patients with type 2 diabetes mellitus.Methods: Eligible subjects from outpatient clinic were recruited and randomized to either intervention group or control group. Inpatients with poor outcomes and complications acted as mentors to share their experience with the intervention group in three tailored classes. Besides, the intervention group received general advice from specialists. The control group received general advice only. The glucose metabolic status and behavior modification indicators were evaluated before and after intervention. In addition, both groups finished a questionnaire survey regarding awareness to diabetic complications after intervention.Results: Eighty-four subjects were recruited (42 subjects for each group), and 51 subjects finished the study. Both the intervention group (n=29) and the control group (n=22) showed a tendency toward a decrease in glycosylated hemoglobin level (A1c, −0.8% vs −0.4%, P<0.05) and improvement in behavior modification (+5.0 vs +2.8, P<0.05) after 6 months. The intervention group (13.8%) obtained a higher percentage than the control group (9.1%) whose A1c reached ≤7%. The body mass index did not change significantly in any group. The questionnaire score about complication awareness was higher in the intervention group than in the control group.Conclusion: This preliminary evidence suggests that PTP education strategy is acceptable for facilitating the outcome of glycemic control. Patient sense of complications may work on A1c reduction. Keywords: patient-to-patient education strategy, diabetes, self-management, A1c